Current Status of Breeding Population of Western Osprey in Abu Dhabi, United Arab Emirate - Shakeel Ahmed; Sálim Javed; Shahid B. Khan; Nouf Al Qadi; Abdullah Al Hamadi; Eissa Al Hamadi (Пернатые хищники и их охрана)
Western Osprey (Pandion haliaetus) is a resident breeding species in the United Arab Emirates (UAE). Osprey breed from December to March on offshore and near-shore islands and coastal sites across the country. Approximately 90% of the breeding population is found in Abu Dhabi Emirate, making it a critical area for conservation efforts. Due to its significance, Western Osprey has been listed as an Endangered (EN) species in the Abu Dhabi Redlist of Species.